Noise reduction method for non-stationary noise of vibration signal of shearer mechanical transmission system. (April 2022) - Mao, Qinghua; Zhang, Fei; Jia, Weipeng; Zhang, Yongqiang; Zhang, Xuhui; Fan, Hongwei
Aiming at the problem that vibration signal of mechanical transmission system of shearer is vulnerable to be interferenced by non-stationary strong noise, a combined method with variational mode decomposition and recursive least squares (VMD-RLS) is proposed for non-stationary noise reduction. Firstly, the vibration signal is decomposed by VMD and the number of decomposition layers is determined according to the principle of minimum energy difference. Then, a dominant criterion of frequency-domain characteristic amplitude is proposed to select invalid intrinsic mode components (IMF, Intrinsic Mode Function). The proportion of the frequency-domain characteristic amplitude of each order IMF component for VMD is calculated. The invalid intrinsic mode functions are selected for reconstruction, and the noise signal after VMD decomposition is obtained. Finally, the noise signal decomposed by VMD is used as reference noise signal of RLS adaptive filtering algorithm to carry out adaptive noise reduction, and the final vibration signal after noise reduction is obtained. The wavelet de-noising method, VMD de-noising method, and VMD-RLS de-noising method are used to carry out noise reduction comparative experiment on the vibration signal of shearer. The experiment results indicate that the noise reduction method of VMD-RLS is better than VMD and wavelet de-noising method. The noise reduction method of VMD-RLS can effectively extract vibration signals from non-stationary strong noise, and provide help for the subsequent fault diagnosis and analysis of shearer mechanical transmission system.